1983
DOI: 10.1021/bi00280a021
|View full text |Cite
|
Sign up to set email alerts
|

Structure of ribonuclease A: results of joint neutron and x-ray refinement at 2.0-.ANG. resolution

Abstract: The structure of ribonuclease A has been refined jointly with the neutron and X-ray data extending to 2.0 A. The results of an earlier X-ray refinement provided the starting model [Wlodawer, A., Bott, R., & Sjölin, L. (1982) J. Biol. Chem. 257, 1325-1332]. The final R factors were 0.159 (X-ray) and 0.183 (neutron) for a model containing all of the atoms expected in the protein, 128 waters, and a phosphate molecule in the active site. The joint refinement necessitated modifications in the orientation of a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 22 publications
3
101
1
Order By: Relevance
“…The intramolecular main chain hydrogen-bonding pattern (Fig. 5 ) is very similar to that seen in RNase A (Wlodawer & Sjolin, 1983), in RNase 1-1 18: 11 1-124 (Martin et al, 1987), and in the two Asp 121 analogs (deMel et al, 1992). When comparing the relative location of corresponding atoms in two structures, a change in bond distance was considered significant if it was greater than 0.30A.…”
Section: Data Collection Structure Determination and Refinementsupporting
confidence: 61%
See 2 more Smart Citations
“…The intramolecular main chain hydrogen-bonding pattern (Fig. 5 ) is very similar to that seen in RNase A (Wlodawer & Sjolin, 1983), in RNase 1-1 18: 11 1-124 (Martin et al, 1987), and in the two Asp 121 analogs (deMel et al, 1992). When comparing the relative location of corresponding atoms in two structures, a change in bond distance was considered significant if it was greater than 0.30A.…”
Section: Data Collection Structure Determination and Refinementsupporting
confidence: 61%
“…A water molecule coincident with WAT 138 is also found in both refined structures of RNase A (Wlodawer & Sjolin, 1983;Borkakoti et al, 1984).…”
Section: Active Site Solvent Moleculesmentioning
confidence: 59%
See 1 more Smart Citation
“…For ribonuclease the starting model was the joint neutron and X-ray structure of Wlodower and Sjolin (1983) with the PDB designation 5RSA. For DHFR, the starting model was the structure of the methotrexate binary complex with the PDB designation 4DFR Filman et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…In RNases such as RNase T1 [27], RNase T2 [28] and RNase A [29], and also in pancreatic DNase I [30] and S1 nuclease [31], histidine has been implicated in the active site of the enzyme. The chemical modification and site-directed mutagenesis used in this study indicated that PRV DNase is a member of the histidine nuclease family and that His$(" is the active-site residue of PRV DNase.…”
Section: Figure 6 Summary Diagram Illustrating Known Functional Featumentioning
confidence: 99%